Crime no cartão postal: narrativas sobre punição e injustiça em o Globo e Extra - Nasi, Lara (2019)
In this thesis, we aim to understand how newspapers from the same media group, O Globo and Extra, narratively configure the crime that leads a cyclist physician to death on a tourist spot at Rio de Janeiro, Brazil. The suspects of the crime are adolescents, just in a moment in which the country is discussing the reduction of legal age. We seek to understand how Journalism, in these two ways of narrating, according to each paper, provide meanings to the event. Epistemologically, the study is between phenomenology and hermeneutics. So, theoretically, the point of view is the one that understands Journalism as a narrative, following Brazilian researchers that studies Paul Ricoeur (1994). The episode that leads the doctor to death is considered an event (QUÉRÉ, 2004), and we discuss its time configuration when narrated. For the analysis, we gathered journalistic articles about the case published on O Globo and Extra, reaching an amount of 328 texts. Our Methods are inspired in the ones proposed by Motta (2013) for Análise Crítica da Narrativa, observing the specificities of the event. Thus, the analysis has been structured comprehending three different moments: a) knowing the time, the place and the narratives mediatic support; b) decompounding the plot in the two newspapers; c) refiguring the meanings. In the first move, we characterize both journals and structure a timeline with all the turn points identified in the narratives, which also takes into account narrative through other media; in the second one the articles from O Globo and Extra are decompound and narratively deconstructed so that, in the third move, we can understand, then, how narratives confer intelligibility to the event. In our last move, the attention is for the intrigue and how it is compound in each one of the newspapers, how the characters are configured, and how the dramatic designs are structured. Lastly, we understand that the newspapers start from a common comprehension for crime and criminality. The point from which the stories are told leads Extra to the past, seeking the cause of the present tragedy, and O Globo to the future, seeking out for punishment, not only for the adolescents that potentially have caused the crime, but for all the juvenile offenders, by the reduction of legal age. The main character in O Globo is the victim of the crime and, in Extra, the suspect. Finally, dramatic design in O Globo is around a demand for punishment and in Extra is around injustice.